Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài

Những câu hỏi liên quan
xmai23
Xem chi tiết
The Moon
Xem chi tiết
Nguyễn Lê Phước Thịnh
5 tháng 1 2022 lúc 8:24

a: =>x=y+11

xy=60

=>y(y+11)=60

\(\Leftrightarrow y^2+15y-4y-60=0\)

=>(y+15)(y-4)=0

hay \(y\in\left\{-15;4\right\}\)

linh ngọc
Xem chi tiết
Savitajoo
Xem chi tiết
Nguyễn Việt Lâm
16 tháng 7 2021 lúc 19:47

a.

\(\Leftrightarrow\dfrac{\sqrt{2}}{2}sin4x+\dfrac{\sqrt{2}}{2}cos4x=\dfrac{\sqrt{6}}{2}\)

\(\Leftrightarrow cos4x.cos\left(\dfrac{\pi}{4}\right)+sin4x.sin\left(\dfrac{\pi}{4}\right)=\dfrac{\sqrt{6}}{2}\)

\(\Leftrightarrow cos\left(4x-\dfrac{\pi}{4}\right)=\dfrac{\sqrt{6}}{2}\)

\(\Leftrightarrow\left[{}\begin{matrix}4x-\dfrac{\pi}{4}=arccos\left(\dfrac{\sqrt{6}}{2}\right)+k2\pi\\4x-\dfrac{\pi}{4}=-arccos\left(\dfrac{\sqrt{6}}{2}\right)+k2\pi\end{matrix}\right.\)

\(\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{\pi}{16}+\dfrac{1}{4}arccos\left(\dfrac{\sqrt{6}}{2}\right)+\dfrac{k\pi}{4}\\x=\dfrac{\pi}{16}-\dfrac{1}{4}arccos\left(\dfrac{\sqrt{6}}{2}\right)+\dfrac{k\pi}{4}\end{matrix}\right.\)

Nguyễn Việt Lâm
16 tháng 7 2021 lúc 19:50

b.

\(\Leftrightarrow\dfrac{\sqrt{3}}{2}sinx+\dfrac{1}{2}cosx=\dfrac{\sqrt{3}}{6}\)

\(\Leftrightarrow cosx.cos\left(\dfrac{\pi}{3}\right)+sinx.sin\left(\dfrac{\pi}{3}\right)=\dfrac{\sqrt{3}}{6}\)

\(\Leftrightarrow cos\left(x-\dfrac{\pi}{3}\right)=\dfrac{\sqrt{3}}{6}\)

\(\Leftrightarrow\left[{}\begin{matrix}x-\dfrac{\pi}{3}=arccos\left(\dfrac{\sqrt{3}}{6}\right)+k2\pi\\x-\dfrac{\pi}{3}=-arccos\left(\dfrac{\sqrt{3}}{6}\right)+k2\pi\end{matrix}\right.\)

\(\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{\pi}{3}+arccos\left(\dfrac{\sqrt{3}}{6}\right)+k2\pi\\x=\dfrac{\pi}{3}-arrcos\left(\dfrac{\sqrt{3}}{6}\right)+k2\pi\end{matrix}\right.\)

Nguyễn Việt Lâm
16 tháng 7 2021 lúc 19:52

c.

\(\Leftrightarrow\dfrac{\sqrt{3}}{2}cosx+\dfrac{1}{2}sinx=-\dfrac{\sqrt{2}}{2}\)

\(\Leftrightarrow cosx.cos\left(\dfrac{\pi}{6}\right)+sinx.sin\left(\dfrac{\pi}{6}\right)=cos\left(\dfrac{3\pi}{4}\right)\)

\(\Leftrightarrow cos\left(x-\dfrac{\pi}{6}\right)=cos\left(\dfrac{3\pi}{4}\right)\)

\(\Leftrightarrow\left[{}\begin{matrix}x-\dfrac{\pi}{6}=\dfrac{3\pi}{4}+k2\pi\\x-\dfrac{\pi}{6}=-\dfrac{3\pi}{4}+k2\pi\end{matrix}\right.\)

\(\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{11\pi}{12}+k2\pi\\x=-\dfrac{7\pi}{12}+k2\pi\end{matrix}\right.\)

The Moon
Xem chi tiết
Nguyễn Lê Phước Thịnh
5 tháng 11 2021 lúc 0:04

bài 1: 

\(\left\{{}\begin{matrix}x+y=57\\4x-2y=6\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}4x+4y=228\\4x-2y=6\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}6y=234\\x+y=57\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}y=39\\x=18\end{matrix}\right.\)

Mvyyy
Xem chi tiết
Sinh Viên NEU
31 tháng 12 2024 lúc 10:59

1 Kai is tired because he stayed up late watching TV

2 Since I have a broken leg, I fell over while I was playing basketball

3 Sehun is going to be late for school as the bus is late

4 Because Lisa was careless, she broke the cup

5 Rose wants to go home since she feels sick

Sinh Viên NEU
31 tháng 12 2024 lúc 11:00

6 Jimin is hungry as he hasn't eaten all day

7 Since plastic bags are very hard to dissolve, they will cause pollution

8 People reuse and recycle bottles and cans as they want to reduce garbage

9 The sea is becoming increasingly polluted since people drop garbage into the sea

10 We shouldn't throw trash onto the water as polluted water can directly do harm to people's health and kill fish

Sinh Viên NEU
31 tháng 12 2024 lúc 11:00

11 Because of her illness, Lisa didn't go to work yesterday

12 Because of missing the first bus, he came to the office 10 minutes late

13 Because of the bad weather, they canceled the trip to the countryside

14 Because of her richness, she lives happily

15 Because of the heavy rain, we didn't go out

Khum coá tên
Xem chi tiết
Khánh Ngọc
Xem chi tiết
HaNa
4 tháng 10 2023 lúc 17:05

4.2 của cậu đeyy:

loading...  

Uyên tú
Xem chi tiết
Kiều Vũ Linh
21 tháng 12 2023 lúc 6:29

Hình mờ quá, em chụp cho rõ lại để đọc được mới giải được

Kiều Vũ Linh
21 tháng 12 2023 lúc 14:50

b) Xem lại đề

d) \(\left|x+\dfrac{1}{3}\right|.\left(x^2+1\right)=0\)

\(\left|x+\dfrac{1}{3}\right|=0\) (do \(x^2+1>0\))

\(x+\dfrac{1}{3}=0\)

\(x=0-\dfrac{1}{3}\)

\(x=-\dfrac{1}{3}\)